If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3/2(x-1/3)-x+1/3(3x-6)=3/2(x+1/3)
We move all terms to the left:
3/2(x-1/3)-x+1/3(3x-6)-(3/2(x+1/3))=0
We can not solve this equation
| 2x-7+5x+3+x=180 | | 3(4x+2)=5(3+3x) | | z+12=8 | | –2(v+12)=–12 | | -2x-2(-5x+13)=14 | | y÷4=2 | | 8r2+1=321 | | 7s+42=180 | | 114+7x+23=90 | | 10x-1=-125 | | 5x^-4x-20=2x^+3x+5 | | 1/6(x+6)=11 | | 12(x)=18(8) | | 14y=(2y) | | 4w=–9+5w | | 1/2(x-1/3)-1/2x=1/3(x+1/4) | | 2,9=14,n | | 4x-1=5x+3-x | | x+x+42+x-46=180 | | 23t+15=473 | | 88=6(6+x) | | c/c-6=5 | | 51=5c+6 | | 9+2x=5× | | 38=-5a-17 | | 4(6x−1)+x=5(5x−1) | | -5y-3y=32 | | -t/3-14=-10 | | 2x^2+3=93 | | -d/5+9=9 | | -11a=-12a=21 | | (x+2)+x+1=2x-3+3(x+4) |